Effects of Kami Guibi-tang in patients with mild cognitive impairment: study protocol for a phase III, randomized, double-blind, and placebo-controlled trial - Hee-Yeon Shin; Tae-Bin Yim; Hye-Min Heo; Geon-Ho Jahng; Seungwon Kwon; Seung-Yeon Cho; Seong-Uk Park; Woo-Sang Jung; Sang-Kwan Moon; Chang-Nam Ko; Jung-Mi Park (BMC Complementary Medicine and Therapies, 2022)
Abstract Background Amnestic mild cognitive impairment (aMCI) is often considered a precursor to Alzheimer’s disease (AD) and represents a key therapeutic target for early intervention of AD. However, no treatments have been approved for MCI at present. Our previous pilot study has shown that Kami Guibi-tang (KGT), a traditional herbal prescription widely used in Korean medicine for treating amnesia, might be beneficial for improving general cognitive function of aMCI patients. We will conduct a larger-scale clinical trial to validate the findings of our pilot study and further examine the efficacy and safety of KGT in aMCI. Methods This trial is designed as a randomized, double-blind, placebo-controlled clinical trial. A total of 84 aMCI patients will be recruited and randomized into the treatment and control groups. Participants will be administered either KGT or placebo granules for 24 weeks, with a follow-up period of 12 weeks after the last treatment. Primary outcomes will include changes in cognitive performance assessed using a neuropsychological test battery, called the Seoul Neuropsychological Screening Battery, between the baseline, post-intervention visit, and follow-up visit (24th and 36th week, respectively). Secondary outcomes will involve the rate of progression to AD, changes in neuroimaging signals assessed using structural magnetic resonance imaging (MRI), resting-state functional MRI (rs-fMRI), and task-based fMRI, and changes in blood biomarkers measured by the ratio of plasma amyloid-β 42/40 levels (Aβ42/Aβ40) between the baseline and post-intervention visit (24th week). For safety assessments, blood chemistry tests and electrocardiograms (ECG) will also be performed. Discussion This study aims to provide confirmatory evidence of the effect of the Korean herbal medicine, KGT, on improving cognitive function in patients with aMCI. We will identify the possible mechanisms underlying the effects of KGT using neuroimaging signals and blood biomarkers. Trial registration Korean Clinical Trial Registry ( https://cris.nih.go.kr/cris/search/detailSearch.do/16918; Registration number: KCT0007039; Date of registration: February 24, 2022).